RESEARCH OF THE CLEANING PROCESS REGULARITIES FOR THE MODEL WASTE WATER SYSTEMS WITH THE «VODOKANALNY» POLYACRYLAMIDE FLOCULANT - Eugeniya Y. Shachneva; Viktor Y. Khentov (Водное хозяйство России: проблемы, технологии, управление)
The article presents for the first time the results of studies on the use of the «Vodokanalny» flocculant for flocculation purification of model wastewater solutions. The process of flocculation of dispersed systems by polyelectrolytes is described. The influence of the nature and concentration of (poly) electrolytes on the flocculation rate was studied using BAU and quartz sand suspensions as an example. Graphical dependences of the described quantities on the concentration of introduced reagents are given. The clarification rates of suspensions in the presence of polyelectrolytes were investigated. The values of the initial particle deposition rates are calculated. The dependences of the value of the cleaning efficiency on the volume of the introduced substance are presented. A comparative analysis of the use of the component with polyacrylamide flocculants of the AK-631 type (A-930 and A-1510) was carried out.